Antiproliferative Activity of Two Copper (Ii) Complexes on Colorectal Cancer Cell Models: Impact on Ros Production, Apoptosis Induction and Nf-Κb Inhibition - Lemus-Chavez, L; Lemus-Chavez, L; Levín-Vásquez, P; Levín-Vásquez, P (Elsevier B.V., 2022)
The main goal of this work was to screen the antiproliferative activity and mechanism of actions of two copper complexes: [Cu(dmp)2(CH3CN)]2+ (1) and [Cu(phen)2(CH3CN)]2+ (2) on 2D and 3D colorectal cancer cells models. Cell viability studies on three colorectal cancer cell lines (HT-29, LS174T, Caco-2) displayed that 1 showed more robust antiproliferative activity than 2 and cisplatin. Intracellular copper content (63.24% and 48.06% for 1 and 2, respectively) can explain the differences in the cytotoxicity assay. ROS production is the primary mechanism of action involved in the antiproliferative activity of 1 showing 4-, 70- and 2.5- fold increased values of ROS level for HT-29, LS174T, Caco-2 cancer cell lines, respectively. This effect takes place along with the depolarization of the mitochondrial membrane at 2 µM. Besides, both complexes increased apoptosis on three cancer cell lines at low micromolar concentrations (0.5–2.5 μM). Moreover, 1 and 2 inhibited NF-κB pathway both in HT-29-NF-kB-hrGFP monolayer (0.5 to 1 μM) and spheroids HT-29 GFP (5 to 10 μM). This inhibitory effect leads to an inactivation of the MMP-9 expression on HT-29 cell line. Altogether, these results showed that 1 exhibits antiproliferative activity on human colorectal cancer cells in the monolayer and the 3D model. © 2021